Expert reviewMechanical circulatory support in cardiogenic shock – what every interventional cardiologist should know - Pyka, Łukasz; Pres, Damian; Przybylski, Roman; Pacholewicz, Jerzy; Poloński, Lech; Zembala, Marian; Gąsior, Mariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Cardiogenic shock (CS) remains the main cause of death in patients with myocardial infarction. Conservative treatment alone does not sufficiently improve prognosis. Mortality in CS can only be significantly reduced with revascularization, both surgical and percutaneous. However some patients present with haemodynamic instability despite optimal medical treatment and complete revascularization, resulting in very high mortality rates. These patients require the implementation of mechanical circulatory support in order to increase systemic blood flow, protect against organ hypoperfusion and protect the myocardium through a decrease in oxygen consumption. In contemporary interventional cardiology it seems that every operator should be aware of all available mechanical circulatory support methods for their patients. This article aims to present the current state of knowledge and technical possibilities in this area.